2014
DOI: 10.1155/2014/260549
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4Aand p14ARFGene Promoter Hypermethylation as Prognostic Biomarker in Oral and Oropharyngeal Squamous Cell Carcinoma: A Review

Abstract: Head and neck squamous cell carcinoma is a heterogeneous group of tumors with each subtype having a distinct histopathological and molecular profile. Most tumors share, to some extent, the same multistep carcinogenic pathways, which include a wide variety of genetic and epigenetic changes. Epigenetic alterations represent all changes in gene expression patterns that do not alter the actual DNA sequence. Recently, it has become clear that silencing of cancer related genes is not exclusively a result of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 56 publications
2
29
0
1
Order By: Relevance
“…Similar findings have also been reported by Chung et al 21 and Lingen et al 13 Integration of HPV oncoproteins, E6 and E7, leads to degradation of tumour suppressors p53 and Rb. 7,22 The loss of Rb leads to the increased expression of p16 INK4A protein, encoded by the tumour suppressor gene, CDKN2A, 23 that can be readily detected using immunohistochemistry 23,24 and is considered a surrogate marker for HPV infection in the oropharynx, uterine cervix, and the anal canal. 3 However, other chromosomal alterations in cell cycle regulators such as p53 and p14 pathways, 23,25 transforming growth factor-b II receptor, 26 CDK4 27 and the epidermal growth factor receptor (EGFR) 28 can cause p16 overexpression independent of HPV as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have also been reported by Chung et al 21 and Lingen et al 13 Integration of HPV oncoproteins, E6 and E7, leads to degradation of tumour suppressors p53 and Rb. 7,22 The loss of Rb leads to the increased expression of p16 INK4A protein, encoded by the tumour suppressor gene, CDKN2A, 23 that can be readily detected using immunohistochemistry 23,24 and is considered a surrogate marker for HPV infection in the oropharynx, uterine cervix, and the anal canal. 3 However, other chromosomal alterations in cell cycle regulators such as p53 and p14 pathways, 23,25 transforming growth factor-b II receptor, 26 CDK4 27 and the epidermal growth factor receptor (EGFR) 28 can cause p16 overexpression independent of HPV as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Kaabi et al postulate that p16 expression prevents cellular proliferation by preventing the progression from the G1 to the S phase in the cell cycle. 23 p16 has also been shown to play an important role in mediating senescence leading to cell death in the setting of genetic damage which may initiate or potentiate neoplasia. 30 Dong et al 31 observed that homozygous p16 deletion was significantly more frequent in pT3 and pT4 tumours as compared to pT1 and pT2 tumours in their cohort of 30 cases of buccal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Using its SRA domain, UHRF1 interacts with histone deacetylase 1 (HDAC1) and DNMT1 [7, 31, 33]. This interaction takes place at methylated promoter regions of several TSGs including p16 INK4A , p14 ARF (known as p19 ARF in mouse), both encoded by the CDKN2A gene [34], and RARalpha [7]. However, to our knowledge no data are so far available in the literature about the consequence on p14 ARF and RAR protein levels [7].…”
Section: Role Of Uhrf1 In the Epigenetic Silencing Of Tsgs In Cancermentioning
confidence: 99%
“…Aberrant methylation in NELL1, TAC1, and FHIT was associated with poor prognosis, and TLSC1 methylation was associated with aggressive tumor IV. CDKN2A (p16) is a promising candidate biomarker for predicting clinical outcome of oropharyngeal squamous cell carcinoma, especially for recurrence-free survival [147]. Patients with high UCHL1 methylation levels had poorer 5-year survival rates and also an increased incidence of lymph nodes metastases versus those with lower methylation values.…”
Section: Othersmentioning
confidence: 99%